Daya infeksi larva filariform ancylostoma sp. Pada anjing setelah pemberian pupuk urea=The Inejfectivity of Filariform Larvae ofg Ancylostoma Sp in Dogs After Reared in Urea Fertilization - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 1988)
ABSTRACT Hookworm infetation is stil considered as an important public health problem in Indonesia. The prenn7Pnce is considerably high (50-80%), especially among farmers and plantation workers. Poor sanitation and personal hygiene, and habits of defecation at any places facilitated the spread of the eggs of the worms, and increase the infection rates. But the intensity of infection usually is low. This might be due to factors which influence the development and infectivity of the larvae, such as: temperature, humidity and pH of the environments. To increase rice production in Indonesia, several efforts have been applie_d. One of them is the utilization of fertilizer. Urea fertilizer is commonly used, Bern its available every where, and its soluble in mater and readily changed into ammonium- carbonate by the acts of bacterius in the soils, and consequently absorbed by plants very easily. The farmers usually used the fertilizer al 200 kg/ha or equivalent to 1,33 g/100 ml water at the time prior to planting, and equivalent to 0,133g/100 ml water at the time after planting. To know the infectivity of the hookwrom larvae, an in vivo study was carried out. The filarifonn larvae of Ancylosloma sp. were given orally to 2 months old dogs. To each dog was given 500 infective larvae collected from each level of urea concentration, and for control dogs were infected with larva collected from culture without urea (aquadest). The results showed that the numbers worms recovered form the intestine of the dogs infected were significantly lowered than those of the control (p ...